The The Effect of Digital and Printed based Texts on Reading Comprehension of Indonesian EFL Students - Haanii Pradini (Jurnal Studi Guru dan Pembelajaran, 2025)
This study examines whether text format screen based (digital) texts versus paper-based (printed) texts affects Indonesian English as a Foreign Language (EFL) students’ reading comprehension, addressing a gap in research comparing these two modes in EFL classrooms. Using a quasi-experimental, non-equivalent control group design, the study involved 60 second-semester agrotechnology students purposively selected based on comparable English proficiency. Participants were assigned to an experimental group (screen-based texts) and a control group (paper-based texts). Both groups completed a pre-test and post-test consisting of a 25-item multiple-choice reading comprehension test. The treatment was implemented during regular classroom sessions in which the experimental group read the assigned materials via digital/screen-based format, while the control group read the same materials in printed form. Data were analyzed using paired-samples t-tests (within-group pre–post change) and an independent-samples t-test (between-group comparison) in SPSS. Results showed that both groups improved from pre-test to post-test, and the experimental group achieved significantly higher post-test performance than the control group (M = 71.83 vs. 66.33; t = 2.976, p = .004). These findings indicate that using screen-based texts can be more effective than paper-based texts for improving EFL students’ reading comprehension in this context. Future studies with larger samples and clearer variation in text features are recommended to strengthen generalizability.